OSIRIS-REx low-velocity particles during outbound cruise. Issue 1 (1st January 2019) - Rizk, B.; Drouet d'Aubigny, C.; Hergenrother, C.W.; Bos, B.J.; Golish, D.R.; Malhotra, R.; Lauretta, D.S.; Butt, J.; Patel, J.; Fitzgibbon, M.; May, C.; Bierhaus, E.B.; et al.
Abstract: We analyzed high-angular rate streaks first recorded by OSIRIS-REx's MapCam during a 2017 search for Earth Trojan asteroids. We interpret them as water-ice particles that translated across the imager's field of view, originating from the spacecraft itself. Their translation velocities approximated 0.1–1 m/s based on reasonable conclusions about their range. Pursuing several lines of investigation to seek a coherent hypothesis, we conclude that the episodic releases of the water ice particles are associated with spacecraft attitudes that resulted in solar illumination of previously shadowed regions. This correlation suggests that the OSIRIS-REx spacecraft itself possesses micro-climatic zones consisting of hot regions and cold traps that may temporarily potentially pass volatiles back and forth before losing most of them.